KAUM MUDA BALI : HARAPAN VS. KENYATAAN - Dayuh Rimbawan I Nyoman (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2013)
It cannot be denied that young people has played important role in Indonesian history since the colonial period until the independence era. Many argue that young people is the nation’s future. But on the other side they face numerous challenges. During the last decade there has been a serious concern of young people behavior, like personal or group fighting, students brawl, drunk, extortion, theft, drug abuse, and free sex. The most prominent issues in Bali are drug abuse and free sex. The Bali community care drugs predicts that 1.3 percent of Balinese population is drug addicts, in which most of them are under 20 of age. Drug addicts would potentially be infected with HIV virus. The number of people with AIDS in Bali is increasing. During the last 27 years there are 7,291 people with HIV/AIDS (3,459 living with AIDS and 3,832 infected with HIV). About 40 percent of them are aged between 20 to 29. Outside Java, free sex is mostly found in Makassar, Denpasar, Medan, and Palembang. Studies that have been conducted in several locations found that 39 percent of respondents aged 15 to 25 stated that they had sexual intercourse. Free sex potentially raises unwanted pregnancy (KTD), various sexual diseases (PMS), as well as infected with HIV virus. According to KPAD Bali (2011) as many as 95 teenagers in Bali are positively infected with HIV virus or living with AIDS. Most of them have the virus through free sex. KTD also potentially causes abortion, which could threat not only the reproduction system of the woman, but also the psychological impact to her. The cases of young people infected with HIV/AIDS, drug abuses and free sex mentioned before might be only the tip of the iceberg. The reality could be even much more cases, because these matters are very sensitive, thus people involved would be relatively more closed.